2013
DOI: 10.3109/10717544.2013.840692
|View full text |Cite
|
Sign up to set email alerts
|

Primaryin vitroandin vivoevaluation of norcantharidin-chitosan/poly (vinyl alcohol) for cancer treatment

Abstract: Two novel polymer-drug conjugates norcantharidin-poly(vinyl alcohol) and norcantharidinchitosan (NCTD-PVA and NCTD-CS) were synthesized via alcoholysis reaction and characterized by 1 H-NMR and FTIR. NCTD was released from the conjugates via hydrolysis, faster in PBS (pH 5.0) than that in PBS (pH 7.4). NCTD-PVA and NCTD-CS inhibited human esophageal carcinoma ECA-109 cell and murine breast cancer EMT6 cell growth in a dose-dependent manner. The IC 50 values of NCTD, NCTD-PVA and NCTD-CS on ECA-109 cell at 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
0
9
0
1
Order By: Relevance
“…The acquired results propose that the cancerous bone cells did not grow in the presence of the incorporated constituents. Li et al showed the inhibition effect of CS or PVA on cancerous cells as NCTD-PVA and NCTD-CS inhibited human esophageal carcinoma ECA-109 cell and murine breast cancer EMT6 cell growth in a dose-dependent manner [30].…”
Section: Mtt Assaymentioning
confidence: 99%
“…The acquired results propose that the cancerous bone cells did not grow in the presence of the incorporated constituents. Li et al showed the inhibition effect of CS or PVA on cancerous cells as NCTD-PVA and NCTD-CS inhibited human esophageal carcinoma ECA-109 cell and murine breast cancer EMT6 cell growth in a dose-dependent manner [30].…”
Section: Mtt Assaymentioning
confidence: 99%
“…The activities of caspase-3, -8, and -9 in SK-Hep-1 cells were assessed based on the specific protease-peptide substrate chromogenic reaction. , In brief, SK-Hep-1 cells cultured in 6-well plates at 4 × 10 5 cells/well were treated for 12 h with PBS (as control) and different concentrations of compound 7 . After that, the cells were harvested, lysed, and centrifugated.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…While NCTD reduces the effects of cantharidin on the urinary system, it remains effective against liver cancer. NCTD has been shown to inhibit the growth of numerous cancer cell lines including liver cancer, esophageal cancer, gastric cancer and other cancers via apoptosis, autophagy and cell cycle arrest [1][2][3][4]. It increases white blood cell count, protects liver cells, regulates immunity, and does not cause bone marrow suppression.…”
Section: Introductionmentioning
confidence: 99%